Redox-mediated functional and structural changes in insulin receptor kinase - Hotz-Wagenblatt, Agnes; Dröge, Wulf (Protein sensors and reactive oxygen species ; B: Thiol enzymes and proteins, 2002)
This chapter describes the methods used to demonstrate redox effects on the structure and function of the insuling receptor kinase (IRK). Under these methods, the chapter describes an experimental protocol showing that treatment of intact Chinese hamster ovary (CHO)-HIR cells with low micromolar hydrogen) enhances tyrosine phosphorylation in response to insulin. The second method is the method of molecular modeling by energy minimization, which predicts moderate structural changes because of slight posttranslational modifications of an already folded protein. The other methods include three-dimensional modeling by energy minimization, identification of permissive and nonpermissive steps in sequential posttranslational modification of IRK domain, insertion of adenylyl imidodiphosphate (AMP-PNP) into ATP-binding site.
Gesehen am 02.02.2021